(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education is a constructive process which drags a person from darkness, poverty and misery and leads him to the pool of prosperity and happiness by developing his personality in the entire aspects i.e. physical, mental social, emotional & spiritual. It is a lifelong process that starts from the birth of the individual and continues till death. A school is a miniature of the society. Both teacher efficiency and school improvement plans are often evaluated by measures of student achievement. It is clear from recent research that teachers have a great potential to affect student’s educational outcomes. Teachers’ efficiency is popularity known as self-efficacy in terms of psychological construct. Teachers Self –efficacy may be defined as his/her belief to achieve desired goal efficiently and effectively.To give your best to others is the nature’s law and Work is Worship, as said by Swami Vivekananda. It is prime responsibility of a teacher to inculcate the students in utmost manner. So a teacher with with high self-efficacy can give his best to his students. Teachers with high self-efficacy can achieve their goals i.e. they are able to bring desirable changes in in students behaviour and their outcomes. Teachers who have high levels of self-efficacy can motivate their students to achieve their goals. In olden days teaching profession was considered as one of the most comfortable job, but the time has changed, now teaching profession has become very challenging. In present education scenario only those teachers can survive who have high levels of self-efficacy.